Unique double concentric ring organization of light harvesting complexes in Gemmatimonas phototrophica - Dachev, Marko; Bína, David; Sobotka, Roman; Moravcová, Lenka; Gardian, Zdenko; Kaftan, David; Šlouf, Václav; Fuciman, Marcel; Polívka, Tomáš; Koblížek, Michal (Public Library of Science, 2017)
The majority of life on Earth depends directly or indirectly on the sun as a source of energy. The initial step of photosynthesis is facilitated by light-harvesting complexes, which capture and transfer light energy into the reaction centers (RCs). Here, we analyzed the organization of photosynthetic (PS) complexes in the bacterium G. phototrophica, which so far is the only phototrophic representative of the bacterial phylum Gemmatimonadetes. The isolated complex has a molecular weight of about 800 ± 100 kDa, which is approximately 2 times larger than the core complex of Rhodospirillum rubrum. The complex contains 62.4 ± 4.7 bacteriochlorophyll (BChl) a molecules absorbing in 2 distinct infrared absorption bands with maxima at 816 and 868 nm. Using femtosecond transient absorption spectroscopy, we determined the energy transfer time between these spectral bands as 2 ps. Single particle analyses of the purified complexes showed that they were circular structures with an outer diameter of approximately 18 nm and a thickness of 7 nm. Based on the obtained, we propose that the light-harvesting complexes in G. phototrophica form 2 concentric rings surrounding the type 2 RC. The inner ring (corresponding to the B868 absorption band) is composed of 15 subunits and is analogous to the inner light-harvesting complex 1 (LH1) in purple bacteria. The outer ring is composed of 15 more distant BChl dimers with no or slow energy transfer between them, resulting in the B816 absorption band. This completely unique and elegant organization offers good structural stability, as well as high efficiency of light harvesting. Our results reveal that while the PS apparatus of Gemmatimonadetes was acquired via horizontal gene transfer from purple bacteria, it later evolved along its own pathway, devising a new arrangement of its light harvesting complexes.
Keywords: BChl; bacteriochlorophyll; CD, circular dichroism; LD, linear dichroism; LH1, light-harvesting complex 1; LH2, light-harvesting complex 2; NIR, near infrared region; PGC, photosynthesis gene cluster; PS, photosynthetic; RC, reaction center